2002
DOI: 10.1097/00005768-200204000-00016
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic analysis of high-speed treadmill sprinting over a range of velocities

Abstract: The results indicated that at slower velocities, there were differences in the stride characteristics and lower-extremity kinematics while sprinting on a treadmill. As the velocity approached near maximum mechanical breakdown was seen, suggesting that velocities greater than 90% should be used selectively during treadmill training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Several previous publications have observed the relationship between measures of leg angular velocity and running speed ( Kivi et al, 2002 ; Kunz and Kaufman, 1981 ; Mann and Herman, 1985 ; Mann and Murphy, 2018 ; Miyashiro et al, 2019 ). Furthermore, faster running speeds have been associated with measures of hip joint strength, power, torque, work and muscle activation ( Belli et al, 2002 ; Bezodis et al, 2008 ; Copaver et al, 2012 ; Deane et al, 2005 ; Dorn et al, 2012 ; Nagahara et al, 2020 ; Schache et al, 2011 ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Several previous publications have observed the relationship between measures of leg angular velocity and running speed ( Kivi et al, 2002 ; Kunz and Kaufman, 1981 ; Mann and Herman, 1985 ; Mann and Murphy, 2018 ; Miyashiro et al, 2019 ). Furthermore, faster running speeds have been associated with measures of hip joint strength, power, torque, work and muscle activation ( Belli et al, 2002 ; Bezodis et al, 2008 ; Copaver et al, 2012 ; Deane et al, 2005 ; Dorn et al, 2012 ; Nagahara et al, 2020 ; Schache et al, 2011 ).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, measurements of leg angular velocity have been positively related to running speed in human sprinting ( Belli et al, 2002 ; Kivi et al, 2002 ; Kunz and Kaufman, 1981 ; Mann and Herman, 1985 ; Mann and Murphy, 2018 ; Miyashiro et al, 2019 ) and cited as a critical factor for running speed in robotic legged locomotion ( Thompson and Raibert, 1989 ). However, despite prior evidence linking faster running speeds to both greater vertical ground reaction force and leg angular velocity, the connection between these two factors has not yet been fully explored across a range of speeds and runners.…”
Section: Introductionmentioning
confidence: 99%
“…Given that one of the fitness tests is completed at maximum running speed, the running intensity is much higher during fitness testing. The upper leg (quadriceps and hamstring) is biomechanically and anatomically more challenged during sprinting than during lower-intensity running [37]. It is therefore logical that studies have found that the quadriceps and hamstring regions are more commonly injured among sprinters than among middle- and long-distance runners [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the lower limb muscles showed higher muscle activity during the stance phase, RF and VL activities during the stance phase did not differ between uphill and level sprint running. These results may be due to the sprint-specific running mechanics of the knee joint [28][29][30][31] . Based on geometrical reasoning, Ito et al 30) have demonstrated that full knee extension during the stance phase cannot lead to efficient development of horizontal running speed.…”
Section: Discussionmentioning
confidence: 99%